SYMBIOTIC FIXATION OF NITROGEN IN BELMONDO PEA VARIETY IN A SUGGESTED CROP ROTATION SYSTEM - TECHNICAL, ECOLOGICAL AND ECONOMIC EFFICIENCY - Mihai BERCA; Valentina-Ofelia ROBESCU; Gabriel CROITORU; Roxana HOROIAŞ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In 2016 and 2017, in southern Romania, field experiences with Belmondo pea variety have been carried out. It has been found that, at about 35 days after emergence, the number of fresh nodules per plant ranged from 20 to 46 in the nitrogen-free version, with an average of about 33 nodules/plant. Since nodules were found at 80 plants/m2, it results a number of 2,640 nodules/m2. By weighing after oven drying, it was measured 38.24 mg/plant, which is 3.06 g/m2 and 30.6 kg/ha. Using the balance (difference) method, the calculated amount of nitrogen extracted from peas was 262.5 kg/ha, as follows: Nbiologically fixed = 262.5 – 135 (control wheat) = 127.5 kg N/ha (2-year average for Belmondo peas). It results that for each kg of dry nodules a quantity of 4.17 kg N has been synthesized – a nitrogen calculation coefficient. In a crop rotation with 25% peas and a surface of 1,600 ha, an amount of 51 t N/ha is fixed, which represents 24.5% or 29.4 €/ha. Research is part of a program meant to reduce conventional inputs and increase farm profitability.